ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH DI DESA PAYA BILI SA KECAMATAN BIREM BAYEUN KABUPATEN ACEH TIMUR - Ulfatul Yuhan; Nurjannah Nurjannah; Rozalina Rozalina; Ichsan Ichsan; Zulfahmi Zulfahmi (LPPM Universitas Malikussaleh - Indonesia, 2022)
Factors affecting paddy rice production in Paya Bili Sa Village, Birem Bayeun District, East Aceh Regency. This research was conducted in Paya Bili Sa Village, Birem Bayeun District, East Aceh Regency. Sampling was carried out using the slovin formula with an error tolerance of 15%, from a total population of 145 people, a sample of 34 people was obtained. Data processing is carried out using SPSS 20 software. The results of statistical analysis with the double linear regression method, obtained the value of Y= 98.734 + 3586.085 X1 + 0.000159 X2 + 0.005696 X3 + 0.000521 X4 + 0.000300 X5. The results of the coefficient of determination (R2) test showed the relationship between the variables of land area, labor costs, seed costs, fertilizer costs and pesticide costs had a very strong effect on paddy rice production, Test t, showed that variables of land area, labor costs, seed costs, fertilizer costs had a significant effect on paddy rice production, while pesticide variables did not affect paddy rice production, For the F test, it was shown that the variables of land area, labor costs, seed costs, fertilizer costs and pesticide costs significantly affected paddy rice production, in Paya Bili Sa Village, Birem Bayeun District, East Aceh Regency.